2015
DOI: 10.3126/jmds.v26i0.24940
|View full text |Cite
|
Sign up to set email alerts
|

Transformation towards Human Resource Information Systems

Abstract: This paper has explored the various factors namely technological factors, organisational factors, environmental factors and psychological factors that influence in the adoption of Human Resource Information Systems (HRIS). The purpose of the paper is to focus on the factors essential for the adaptability and capability of companies to accept the introduction of information systems like HRIS. The paper is descriptive in nature and the respondents are the users of HRIS in small, medium and large scale companies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Moreover, when considering human capital management, HRIS plays a vital role. According to (Anitha & Aruna, 2015), HRIS is the bridge to merge HR and IT.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, when considering human capital management, HRIS plays a vital role. According to (Anitha & Aruna, 2015), HRIS is the bridge to merge HR and IT.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Moreover, the HRIS creates a platform for decision-makers to find the information for their decisions. The research scholar of (Anitha & Aruna, 2015) mentioned that from the 1960s onwards, organizations used electronic practices for personal management concerning the functions of planning, administration, coordination, and control. The previous research of (Kagehi S. j., 2015) found that organizational characteristics, IT planning, corporate culture highly influence the execution of HRIS in the IT firms in Kenya.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations